The teaching and learning approaches of Prophet Muhammad (peace be upon him) - Hashim, Che Noraini (2011)
Globalization has brought about many drastic changes in our life including in education. The explosion of information and communication technologies, advancement in educational researches and practices have compelled teacher to be more sensitive to change. They need to consistently improve their teaching quality. The traditional lecture method of ‘talk and chalk’ and the ‘trial and error’ method are in adequate to produce excellent students today. Although many teachers have been exposed to different theories and methods of teaching and learning, the outcomes have not been promising. This paper discusses the approaches, strategies and methods such as halaqah, lecture, demonstration and story telling, that have been used by the Prophet Muhammad (pbuh) to obtain on how to obtain a generation of unique, God-conscious individuals and some proposition on how to obtain optimum results in learning.